Alternative dispute resolution in civil justice systems - Hartley, Roger E., 1969- (American legal institutions., 2002)
Annotation Hartley examines the introduction of alternative dispute resolution (e.g., mediation) in a court system in Georgia. Attorneys supported the introduction of mediation to consolidate control of the legal process and to add it to their practices. They also used mediation to settle some cases more quickly. Mediation gave judges flexibility to weed out minor cases and process others more quickly. However, these changes were not so great as to put a dent in settlement or trial rates, and Hartley concludes that while changes in court procedures have effects, researchers need to examine the behavior of actors in depth in order to discover these effects.